2021
DOI: 10.1039/d1nj02842a
|View full text |Cite
|
Sign up to set email alerts
|

Can surface capping ligands probe cation exchange in inorganic nanoparticles?

Abstract: Cation exchange by post-synthetic modification of inorganic nanoparticles (NPs) are commonly monitored by probing alterations of NP’s core, and not much is known on surface capping ligand’s ability to probe...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…41 In one of our recent works, by systematically monitoring the NPs in the presence and absence of cation exchange, we have demonstrated that the infrared absorption of the surface capping ligand 1-thioglycerol (1-TG) can track the cation exchange reaction in both the ZnS and Zn(Tb)S NPs. 37 This study further emphasizes the fact that the involvement of surface atoms in initiating cation exchange in inorganic NPs propagates into the surface capping ligand, hence including them in the reaction zone as well. An involvement of the entire structure of 1-TG covering both the terminal groups and backbone bonds is involved, as monitored by the tuning of the IR absorption of OH stretching, OH in-plane bending, CH 2 in-plane bending, C–C stretching/C–O stretching, OH out-of-plane bending, and C–S stretching vibrations.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…41 In one of our recent works, by systematically monitoring the NPs in the presence and absence of cation exchange, we have demonstrated that the infrared absorption of the surface capping ligand 1-thioglycerol (1-TG) can track the cation exchange reaction in both the ZnS and Zn(Tb)S NPs. 37 This study further emphasizes the fact that the involvement of surface atoms in initiating cation exchange in inorganic NPs propagates into the surface capping ligand, hence including them in the reaction zone as well. An involvement of the entire structure of 1-TG covering both the terminal groups and backbone bonds is involved, as monitored by the tuning of the IR absorption of OH stretching, OH in-plane bending, CH 2 in-plane bending, C–C stretching/C–O stretching, OH out-of-plane bending, and C–S stretching vibrations.…”
Section: Introductionmentioning
confidence: 57%
“…Their signatures were not evident in the FTIR spectra. 25,37 This post-synthetic protocol of Zn(Tb)S NPs with [Zn(Tb)S] : [Pb 2+ ] ratio of 1 : 10 −4 , 1 : 10 −2 , and 1 : 1 resulted in cubic Zn(Tb)(Pb)S, Zn(Tb)(Pb)S, and Pb(Tb)S NPs with 3.0 ± 0.5, 3.2 ± 0.4, and 3.9 ± 0.6 nm (average ± standard deviation) diameter, respectively. 24…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…EDS is used to determine the elemental composition of nanomaterials. ,,,, The elemental composition of Ca­(Ln)­F 2 [Ln = Tb, Eu], as determined from the EDS measurements, reveals atomic percentages of Ca:Ln (Tb/Eu):F = 32.0 ± 2.0:3.6 ± 0.3:64.4 ± 2.2 and 37.8 ± 2.1:3.6 ± 0.2:58.6 ± 2.2, respectively. Co-doped Ca­(TbEu)­F 2 and Ca­(TbGd)­F 2 particles show elemental compositions of Ca:Tb:Eu/Gd:F = 29.4 ± 2.1:3.1 ± 0.2:3.6 ± 0.2:63.9 ± 2.3 and 28.5 ± 0.3:3.0 ± 0.2:2.8 ± 0.1:65.7 ± 0.3, respectively.…”
Section: Resultsmentioning
confidence: 99%